The Impact of Hygiene and Motivator Factors on Job Satisfaction: A Case Study of Laboratory Professionals in Islamabad - Khan, Matee ur Rehman; Khalid, Maryam; Tabassum, M. Taha; Mukhtar, Nimra; Hamza, Mirza M.; Shah, Hassan; Begum, Shahzeera; Hashmi, Mahe-Kamil Qureshi (Indus Journal of Bioscience Research, 2025)
Objectives: To find out how hygiene factors like salary, working conditions, and organizational policies, and motivator factors such as recognition, achievement, and growth opportunities affect job satisfaction among lab professionals, using Herzberg's Two-Factor Theory. To check how well the basic needs of lab professionals like physiological, safety, social, esteem, and self-actualization needs are being fulfilled at their workplace, based on Maslow's Hierarchy of Needs, and how these needs are linked to their overall job satisfaction. Methodology: Study Setting: The study was carried out among lab professionals working at Al Nafees Medical College (ANMC) and partnered hospitals in Islamabad. Study Design: A cross-sectional study was conducted using a questionnaire that included both open-ended and closed-ended questions. This helped collect both detailed and statistical data from participants. Sampling Technique: Random sampling was used to select lab professionals from different hospitals in Islamabad. Sample Size: A total of 328 medical laboratory professionals took part in the study. Study Duration: The data collection took 6 months, starting from 26th June 2024 to 23rd December 2024. Data Analysis: Data were analyzed using SPSS version 27. Descriptive statistics like frequencies and percentages were used to summarize the responses. Results: The findings showed that job satisfaction among lab professionals in Islamabad was moderate. Out of 328 participants, 126 (38.4%) were satisfied with their salary, while 78 (23.7%) were not. In comparison, 150 (45.7%) were satisfied with their responsibilities, and 151 (46%) felt satisfied with their achievements. However, 112 (34%) were not satisfied with their job security. Regarding basic needs, 128 (39.4%) of participants said their physiological needs were met, while 149 (45.4%) felt their social needs were fulfilled. On the other hand, 126 (38.4%) were dissatisfied with their safety needs. These results highlight important areas that need improvement to increase job satisfaction and help healthcare institutions retain qualified laboratory staff. Conclusion: The study concluded that job satisfaction among medical laboratory professionals is influenced by both hygiene factors and the fulfillment of needs described in Maslow’s theory. The results showed that while many professionals are satisfied with growth and recognition, concerns remain around salary and job security. Addressing both types of factors is important to improve job satisfaction and create a better working environment for lab professionals.